Perceived needs of the bereaved during acute grief : Pilotní případová studie vybrané organizace (Paliativní medicína, 2024)
The paper answers the question: What are the needs of the bereaved in the acute phase perceived by the workers who come into contact with them? First, acute bereavement is defined as an immediate response to the death of a loved one, and the help that is considered to support coping with the acute phase of bereavement is presented. This is based on the principles of coping support, problem-solving, and trying to promote a positive worldview. A qualitative pilot study based on the implementation of two mini-focus groups presents the identified five needs (information-decision-making, coping, validation, guilt management, and contact) of acutely bereaved people. The last two mentioned tend not to fit the task-focused concept of supporting the acute phase of grieving. This could place a request for services for acutely bereaved to think about how to support those needs as well.
Keywords: Acute Grief; Needs; Bereavement; Grief Counseling; Support